ANALISIS PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN TERHADAP PELAKU TINDAK PIDANA PEMBUAT IJAZAH PALSU DI INSTITUT AGAMA ISLAM MA’ARIF NAHDLATUL ‘ULAMA (IAIM-NU) NU METRO - Sinaga, Hasudungan (IBLAM LAW REVIEW, 2023)
There are several forms of counterfeiting crimes, which are regulated in the provisions of Indonesian criminal law, including counterfeiting money, counterfeiting brands, and so on. The research problem is: What are the factors causing the criminal act of making fake diplomas at the Ma'arif Nahdlatul 'Ulama Islamic Institute (IAIM NU) NU Metro and what is the basis for the judge's consideration in handing down a decision against the perpetrator of the crime of making fake diplomas at the Ma' Islamic Institute? arif Nahdlatul 'Ulama (IAIM NU) Nu Metro. The research method is normative and empirical juridical, using secondary data and primary data, obtained from literature studies and field studies, and qualitative juridical data analysis. Economic factors are the strongest factors that cause criminal acts to occur. The judge's basic consideration in handing down a decision on the crime of diploma forgery is based on criminal evidence through positive legal rules, as well as the judge's knowledge and experience. It is hoped that the police will provide more education to the public, especially young people, so that they do not use shortcuts to earn income, because criminal acts are very detrimental to themselves and others. The aim of imposing a sentence is to deter the perpetrator so that he does not repeat his actions again, but in addition to the maximum sentence, it is hoped that the panel of judges will also provide special mental assistance so that the perpetrator will feel ashamed if they have to deal with the law again.